Flipped Classroom Sebagai Implementasi Teknologi Dalam Meningkatkan Efektivitas Dan Hasil Belajar Mahasiswa Universitas Negeri Makassar - Muhammad Fajar B; Hastuti; Muhammad Farham Saputra; Wilda Inaya Syafdwi; Putri Nanda Sari; Muhammad Fardhan (Sakura Digital Nusantara, 2023)
The field of education, began to be affected by technological advances that are currently developing rapidly. Teachers and students will find it easier to carry out the teaching and learning process with technology. One of the implementers of technology is the use of the Flipped Classroom learning method. Flipped Classroom learning is a teaching and learning method where students participate in class while watching video lessons from outside the classroom through distance learning. A learning strategy known as